Generalized Fubini Apostol-Type Polynomials and Probabilistic Applications - Rabab S. Gomaa; Alia M. Magar (International Journal of Mathematics and Mathematical Sciences)
The paper aims to introduce and investigate a new class of generalized Fubini-type polynomials. The generating functions, special cases, and properties are introduced. Using the generating functions, various interesting identities, and relations are derived. Also, special polynomials are obtained from the general class of polynomials. Finally, probabilistic applications and some probabilistic properties are obtained.